Peran Dinas Pendidikan Pemuda dan Olahraga Dalam Meningkatkan Sarana Prasarana Pengembangan Atlit di Kabupaten Kepulauan Talaud - Gagola, Deivanly; Ruru, Joorie Marhaen; Pombengi, jericho Danga (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRAC: In accordance with the results of research in the field shows that the coaching of athletes inthe District Talaud islands are less sustainable. Athletes only get awards and a variety of services in the lastevent of the championship, after the completion of the event and there is no longer a championship, then ingeneral the athlete is no longer considered and will be sought at the time held more championships. It is animportant task for local governments in general and the Department of Education Youth and Sports inparticular that would be an assurance for athletes who have the name of the area.This type of research is qualitative, focusing on the field of research in the form of case studies (casestudy) directly to the Department of Education Youth and Sports Talaud Islands. Informants were taken asmany as 13 people, which is 5 employees Department of Education Youth and Sports, 4 athletes and 4 membersof the public. The focus of research is more emphasis on the availability of infrastructure as the primary meansof supporting the success in the development of athletic performance.Not optimal role of the Ministry of Youth and Sports in guidance increase athletic performance as wellas the lack of attention in the provision of facilities and infrastructure development of athletes. development ofnational sport is still first, just as a routine oriented instant achievement based on past experience poorinnovation. That is what causes athletes Talaud Islands minimal achievements both at the provincial andnational level. Therefore it needs financial support in supporting the activities of athletic performance, localgovernment more organized and held sporting-iven championship-scale regional and national, furtherenhanced the development of advice infrastructure supporting sport in this case is a gymnasium complete withthe football stadium and other facilities necessary reward for athletes who excel through appointedAdministrative State Civil or provide housing facilities that simple.Key words: The Role of Local Government, Facilities and Infrastructure Development of Athletes